Intramuscular short‐chain acylcarnitines in elderly people are decreased in (pre‐)frail females, but not in males. Issue 9 (16th July 2020) - van der Hoek, Marjanne D.; Nieuwenhuizen, Arie G.; Kuda, Ondřej; Bos, Paul; Paluchová, Veronika; Verschuren, Lars; van den Hoek, Anita M.; Kleemann, Robert; Veeger, Nic J. G. M.; van der Leij, Feike R.; Keijer, Jaap
Abstract: This study tested the hypothesis that in human aging, a decreased intramuscular acylcarnitine status is associated with (pre‐)frailty, reduced physical performance, and altered mitochondrial function. We used a cross‐sectional study design with well‐matched fit and (pre‐)frail old males and females, using young males and females as healthy controls. Frailty was assessed according to the Fried criteria and physical performance was determined by 400 m walk test, short physical performance battery and handgrip strength. Muscle and plasma acylcarnitine status, and muscle mitochondrial gene expression was analyzed. Results showed that intramuscular total carnitine levels and short‐chain acylcarnitine levels were lower in (pre‐)frail old females compared to fit old females and young females, whereas no differences were observed in males. The low intramuscular short‐chain acylcarnitine levels in females correlated with low physical performance, even after correction for muscle mass (%), and were accompanied with lowered expression of genes involved in mitochondrial energy production and functionality. It is, therefore, concluded that in (pre‐)frail old females, intramuscular total carnitine levels and short‐chain acylcarnitine levels are decreased, and this decrease is associated with reduced physical performance and low expression of a wide range of genes critical for mitochondrial function. The results stress the importance of taking sex differences into account in aging research.